Estratégias visando o uso sustentável de água salina em um ciclo de rotação cultural feijão-de-corda/girassol - Neves, Antônia Leila Rocha (2012)
The world population growth and increasing demand for water to meet household consumption and other sectors of the economy, have awakened for the use of alternative sources or water of inferior quality, such as saline water and wastewater. The aim of this study was a preliminary assessment of the situation of desalination plants installed by the State Government of Ceara in the region of Pentecoste, Ceará, and then to evaluate irrigation management strategies (cyclic use of saline water, mixture of water of different salinities and use only in stages of tolerant phase of crop) and the system of crop rotation cowpea/sunflower, aiming at the sustainable use of saline water in irrigated agriculture. The experiment with the cowpea was conducted in the dry season of 2011, and followed the randomized block design, with thirteen treatments and five replications. The treatments were: T1: low salinity water (A1), throughout the cycle, T2, T3 and T4: Water with CE 2.2 (A2), 3.6 (A3) and 5.0 (A4) dS m-1, throughout the cycle, T5, T6 and T7: Water with EC of 2.2, 3.6 and 5.0 dS m-1 in the final phase of the cycle, T8, T9 and T10: Use cyclic A1 and A2, A1 and A3 and A1 and A4, starting with A1 at sowing, T11, T12 and T13: Water of EC of 2.2, 3.6 and 5.0 dS m-1 after germination until the end of cycle. To verify the residual effect of saline water applied during the experiment with the cowpea, sunflower was grown in the rainy season of 2012 in the same plots that were cultivated with cowpea, using supplementary irrigation with water of low salinity. The EC of the desalination waste in the region of Pentecoste ranged from 4.2 to 7.6 dS m-1, representing a risk for the environment, where much of the waste generated is used to feed the vast majority of population is not aware if the reject cause any harm to human health or to the environment. The results of field experiments showed that the use of saline water during the entire cycle of the cowpea up to the level of 5.0 dS m-1 and after germination until the end of the cycle inhibits leaf gas exchange, extraction of nutrients, plant growth and crop yield, while the strategies of irrigation with saline water in the final phase of the crop cycle (flowering and fruiting) and cyclically not negatively affect these variables. Further, these strategies allow a saving 34-47% water of low salinity used for irrigation. There was accumulation of salts in the soil for the cultivation of cowpea of the treatments which used water of high salinity. However, the use of strategies for managing the application of alternating high and low water salinity crop cycle and application of the salt water only in the final stage reduced the impact on soil. The irrigation water of low salinity (0.5 dS m-1) promoted excessive leaching of salts in the soil at the end of sunflower cultivation, but the amount of rainfall before seeding was not sufficient to completely eliminate the residual effect of salinity in the crop.